A Chinese Case of Coronavirus Disease 2019 (COVID-19) Did Not Show Infectivity During the Incubation Period: Based on an Epidemiological Survey - Jong-Myon Bae (Korean Society for Preventive Medicine, 2020)
Controversy remains over whether the coronavirus disease 2019 (COVID-19) virus may have infectivity during the incubation period before the onset of symptoms. The author had the opportunity to examine the infectivity of COVID-19 during the incubation period by conducting an epidemiological survey on a confirmed patient who had visited Jeju Island during the incubation period. The epidemiological findings support the claim that the COVID-19 virus does not have infectivity during the incubation period.